United States Involvement in Economic and Military Sector in the First Gulf War Between Iraq-Iran (1980-1988) - Sumiyatun Sumiyatun; Selly Selly; Kuswono Kuswono (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2022)
The purpose of this study is to describe the background of the First Gulf War in 1980-1988, the involvement of the United States in the economic field in the First Gulf War in 1980-1988, the involvement of the United States in the military field in the First Gulf War in 1980-1988, and the impact of the war. Bay I for the international world. This study uses the historical method, namely topic selection, heuristics, external and internal criticism, interpretation, and historiography. The results of the study are the background of the first Gulf War caused by various causes and factors, both internal and external, both from Iraq and Iran. However, the main factors causing the outbreak of the First Gulf War were the desire to become the dominant country in the region and the Islamic Revolution in Iran which caused upheaval in the region, especially for Iraq and Iran. During the 8 year war between Iraq and Iran, the United States has been involved in the economic field and was seen throughout the war. The war had an impact on the international community, especially the impact on the economy, because it caused world oil prices to soar.